1-De-oxy-l-mannitol (6-de-oxy-l-mannitol or l-rhamnitol). - Jenkinson, S; Booth, K; Gullapalli, P; Morimoto, K; Izumori, K; Fleet, G; Watkin, D (2008)
The crystalline form of 1-de-oxy-l-mannitol, C(6)H(14)O(5), exists as an extensively hydrogen-bonded structure with each mol-ecule acting as a donor and acceptor for five hydrogen bonds. There are no unusual crystal-packing features; the absolute configuration was determined from the use of 6-de-oxy-l-mannose (l-rhamnose) as the starting material.